Assessment of the Swelling Behavior of NaOH-Contaminated Red Earth in the Visakhapatnam Region of India Using X-ray Diffraction Analysis - Srikanth Satish Kumar Darapu and Sai Kumar Vindula (Nature Environment and Pollution Technology, 2024)
Research on the impact of alkali contamination on the swelling behavior of red earth in the Visakhapatnam region has been notably limited. Therefore, this study aims to investigate the effects of alkali (NaOH) contamination on the swelling characteristics of the region’s red earth. The red earth of this region was found to be a well-graded sandy soil with 81% sand and 18% fines. X-ray diffraction studies showed that this region’s red earth mainly consists of quartz, kaolinite, and hematite. The soil is inherently non-swelling. However, the free swell tests showed considerable swell under contamination of NaOH solutions of various normalities (0.05, 0.1, 1, 2, and 4N). One-dimensional consolidation tests have shown that the swell increased with the concentration of the NaOH solution and with the duration of the interaction. Red earth exhibited 'an equilibrium swelling' of 5.6, 10, 15, 17, and 20% when contaminated with 0.05, 0.1, 1, 2, and 4N NaOH solutions, respectively. XRD studies revealed that the red earth sample contaminated with even 0.05N NaOH solution and cured for 56 days exhibited the formation of zeolites analcime and natrolite. Silicate minerals like paragonite and ussingite were also formed along with the zeolites. N-A-S-H compounds, hydrosodalites, and zeolites like super hydrated natrolite, zeolite SSZ16, and zeolite ZK-14 were formed at higher normalities of NaOH after a curing period of 56 days, which caused increased swell. The research demonstrated that the formation of zeolites resulting from the alkali contamination led to swelling in the red earth.